2020
DOI: 10.1111/eje.12559
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of a measure of acceptance of new technologies (UTAUT), applied to the use of haptic virtual simulators in dental students

Abstract: Dental education includes the development of manual skills to perform tasks needed to train students to drill for the elimination of caries or for restorative purposes. 1 Historically, cadaver teeth have been used to train dental students in these drilling procedures but, for ethical, legal and biological reasons, 2 they have been replaced by artificial teeth made of plastic. 1,3 Contemporary technology allowed the development of haptic virtual simulators (HVS); in recent years, their use has been growing expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Finally, 36 articles were included for final analysis and 11 articles were excluded after full text read, for the following reasons: Description of haptic simulator development process 9–12 ; haptic exercise/tooth simulation design 13–17 ; haptics in other specialties or indirectly related psychometrics 18,19 . The PRISMA flow diagram 20 is presented in (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 36 articles were included for final analysis and 11 articles were excluded after full text read, for the following reasons: Description of haptic simulator development process 9–12 ; haptic exercise/tooth simulation design 13–17 ; haptics in other specialties or indirectly related psychometrics 18,19 . The PRISMA flow diagram 20 is presented in (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The main questions in such questionnaires are whether the students think that the simulator assisted their study, improving their understanding of the related curriculum, and whether they are willing to use the simulator in their future study [70]. In addition, Venkatesh et al made the Unified Theory of Acceptance and Use of Technology questionnaire proposal to measure the acceptance of a new technology [71], and Bravo et al applied it to the use of dental simulators and concluded that it can assess the acceptance of dental simulators in dental education [72].…”
Section: Questionnairesmentioning
confidence: 99%
“…A number of models have been used to predict factors associated with the behavioral intention of m-Health [23][24][25][26][27]. Recently, UTAUT is considered as the most valid technology acceptance model used to assess behavioral intention and actual use behavior of m-Health [28][29][30][31][32]. Previous studies have shown that users' behavioral intention of information technology is the basic premise of users' use behavior [33,34].…”
Section: Introductionmentioning
confidence: 99%